Theoretical and experimental analytical study of powertrain system by hardware-in-the-loop test bench for electric vehicles. (2017) - Li, Yong; Xu, Xing; Sun, Xiaoqiang; Xue, Hongtao; Jiang, Haobin; Qu, Yaping
The powertrain system in electric vehicle delivers the energy from the hybrid energy storage system (HESS) to wheels, during which the energy transforms between electricity and mechanical energy. The powertrain system determines the energy conversion efficiency of the HESS. Necessary investigation on the powertrain system should be done before further study on the HESS. The dynamic model of the powertrain system is established and validated both in Psim and Matlab/Simulink software. The control strategy of the traction motor of the powertrain system is verified in virtual vehicular environment firstly. The control approach is implemented on a dSPACE-based hardware-in-the-loop (HIL) test bench for real-time control. The simulation and experimental data both demonstrate the velocity trajectory of the drive cycles are exactly tracked. The efficiency of powertrain system is also investigated. The work in this paper provides solid foundation for further study on power split of the HESS.